2011
DOI: 10.1007/s00484-011-0425-6
|View full text |Cite
|
Sign up to set email alerts
|

Predicting favorable conditions for early leaf spot of peanut using output from the Weather Research and Forecasting (WRF) model

Abstract: Early leaf spot of peanut (Arachis hypogaea L.), a disease caused by Cercospora arachidicola S. Hori, is responsible for an annual crop loss of several million dollars in the southeastern United States alone. The development of early leaf spot on peanut and subsequent spread of the spores of C. arachidicola relies on favorable weather conditions. Accurate spatio-temporal weather information is crucial for monitoring the progression of favorable conditions and determining the potential threat of the disease. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 27 publications
(37 reference statements)
0
14
0
Order By: Relevance
“…Weather fronts and incipient thunderstorms are reported to discourage the mass flight of thrips, thereby resulting in high densities above the soil surface due to the landing attempts of thrips (Kirk, 2004;Lewis, 1964Lewis, , 1965Lewis, , 1973Lewis, , 1997, while Morsello et al (2008) also found that the number of thrips captured in flight has a positive relationship with the number of wet days or days with precipitation. In peanut, populations of adult thrips vectors F. occidentalis and F. fusca were reported to be greater for early planting (Olatinwo et al, 2012). in April or late planting in June compared to planting in May (Mitchell and Smith, 1991;Todd et al, 1995). Field observations also indicate a higher level of spotted wilt associated with early-and late-planted peanuts compared to those planted during the middle of the planting season (Brown et al, 2005bOlatinwo et al, 2008).…”
Section: Case Study 2: Wrf Model and Thrips-vector Populationsmentioning
confidence: 61%
See 4 more Smart Citations
“…Weather fronts and incipient thunderstorms are reported to discourage the mass flight of thrips, thereby resulting in high densities above the soil surface due to the landing attempts of thrips (Kirk, 2004;Lewis, 1964Lewis, , 1965Lewis, , 1973Lewis, , 1997, while Morsello et al (2008) also found that the number of thrips captured in flight has a positive relationship with the number of wet days or days with precipitation. In peanut, populations of adult thrips vectors F. occidentalis and F. fusca were reported to be greater for early planting (Olatinwo et al, 2012). in April or late planting in June compared to planting in May (Mitchell and Smith, 1991;Todd et al, 1995). Field observations also indicate a higher level of spotted wilt associated with early-and late-planted peanuts compared to those planted during the middle of the planting season (Brown et al, 2005bOlatinwo et al, 2008).…”
Section: Case Study 2: Wrf Model and Thrips-vector Populationsmentioning
confidence: 61%
“…According to Grichar et al (2005), other systems have used a similar combination of relative humidity/leaf wetness and temperature to forecast favourable conditions for disease development and scheduling of fungicide applications. Olatinwo et al (2012) demonstrated the possibility of coupling the high-resolution WRF data output with a leaf spot disease model, i.e. Oklahoma peanut leaf spot model in predicting favourable conditions for early leaf spot infection.…”
Section: Case Study 1: Wrf Model and Early Leaf Spot In Peanutmentioning
confidence: 99%
See 3 more Smart Citations